(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Medieval Muslim philosopher al-Farabi’s social utopia «Virtuous city» and public figure XIX-XX centuries, Educator of the Crimean Tatars, the founder of Jadidizm Ismail Gasprinsky’s social utopia»Country of Bliss» were compared in this article. Al-Farabi’s philosophy and Ismail Gasprinsky’s heritage formed under the influence of intercultural dialogue. Al-Farabi synthesized the ancient and the Arab-Muslim philosophical traditions. Ismail Gasprinsky’s social model combines achievements of Europe and Islamic spirituality. We used historical and philosophical method. We used al-Farabi’s treatises «Designation the way to happiness», «Aphorisms of the Statesman», «Achievement of happiness», «Civil Politics», «The attitude of philosophy for religion», «Treatise on the views of residents virtuous city», «About views of Virtuous city’s people». We analyzed Ismail Gasprinsky’s utopia «Country of Bliss» and used his composition «French letters». The composition contained information about «Dar al-Rahat» («Country of Bliss»). There is humanism, the concept of «happiness» as a general objective of achieving a new level of social relations and culture, the idea of an enlightened ruler, etc. Key words: ideal state, social utopia, virtuous city, humanism, happiness, governor, politics, Islam.